REHABILITACJANordic walking as a new model of pulmonary rehabilitation of patients referred for lung transplantation – a preliminary report - Ochman, Marek; Jastrzębski, Dariusz; Wojarski, Jacek; Żegleń, Sławomir; Kowalski, Kamil; Wyrwoł, Justyna; Lutogniewska, Wanda; Maksymiak, Małgorzata; Książek, Bożena; Margas, Anna; Małota, Roksana; Kubicki, Piotr; et al. (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
The benefits of pulmonary rehabilitation (PR) in individuals with chronic lung diseases such as chronic obstructive pulmonary disease (COPD), cystic fibrosis (CF) and interstitial lung disease (ILD) have been well documented. Yet evidence-based guidelines for PR in pre- and post-lung transplant patients have not been developed. In this study the authors present preliminary results of an observational cohort study of pulmonary rehabilitation with Nordic walking (PR-NW) in patients referred for lung transplantation in Poland. In a small group of patients (10 pts), after 12 weeks of PR-NW the authors observed significant improvement in the distance walked in the 6min walk test (6MWT) without any adverse events. It appears that exercise is safe and beneficial for people with severe end-stage chronic lung disease who are awaiting lung transplantation and Nordic walking should be recommended for future research in this patient population.